Validitas dan Praktikalitas Modul Hukum-Hukum Dasar Kimia Berbasis Pendekatan Saintifik dengan Menerapkan Teknik Probing Prompting untuk Siswa Kelas X SMA atau MA - Yuni Purnama Sari; Fauzana Gazali (Edukimia, 2019)
The Implementation of the curriculum is carried out by practicing process skills that are reflected in learning activities. The process skills applied in the form of 5M activities are known as the scientific approach. This research aims to produce of modul of basic chemical laws based on a scientific approach by applying probing prompting techniques. The research instrument used was a questionnaire of validity and practicality. The module was validated by 5 validators while the practicality test was carried out by 2 chemistry teachers and 20 XI grade students of MIA 3 SMAN 1 Basa Ampek Balai Tapan, Pesisir Selatan. Data from the validity and practicality test results were analyzed using the cohen kappa formula. Based on the results of the study, it was found that the average kappa moment of validity test was 0,89 with a very high validity category and the average kappa moment of teacher practicality was 0,90 and the average kappa moment of students practicality was 0,91 with a very high practicality category. Thus, it was concluded that basic chemical laws module based on a scientific approach by applying probing prompting techniques was valid and practical for high school students.